"Алиса" для малышей: сказочная повесть / Л. Кэролл - Кэролл Льюис (Детская библиотека, 2016)
Экземпляры: (20160524) / Инвентарный номер: 39317 / Цена: 78.00 / Авт.знак: К 98 / ГРНТИ: 17 / ББК: 84(4Вел)